Spleen and peripheral blood immunopathology in an outbred model of adult-stage murine schistosomiasis - Schulze, Thomas T.; Neville, Andrew J.; Ehrhorn, Evie G.; Alsuleiman, Sarah A.; Vennerstrom, Jonathan L.; Davis, Paul H. (Frontiers in Immunology, 2025)
Schistosomiasis, a parasitic disease caused by flatworms of genus Schistosoma, is a neglected tropical disease that causes significant morbidity in the developing world. Despite numerous efforts to eradicate the disease, the parasite remains a significant global burden, particularly within Sub-Saharan Africa. Schistosoma species possess an arsenal of potent mechanisms to defend against direct attack from host immune cells and a remarkable ability to modulate the host immune system through proximal and systemic modes that facilitate its stage-specific development, survival, and reproduction. Standardized animal models have been developed that serve as an important resource for dissecting parasite and host immunobiology and for drug and vaccine efficacy studies. However, a comprehensive understanding of the immune responses to Schistosoma mansoni in the standard outbred Swiss Webster mouse model is still lacking, particularly with the granulocyte composition of the spleen and the associated blood cytokine responses that occur during chronic infections. To continue characterization of this important secondary lymphoid tissue and the peripheral blood, we examined infected mouse spleens and additionally performed a detailed flow cytometric analysis of the splenic compartment from infected mice with specific attention to granulocytes and Th2-associated leukocytes. Peripheral blood from infected animals was used to evaluate a panel of Th1- and Th2-associated cytokines for comparison. Lastly, an analytical blood count and differential was also reported to provide a case study of late-stage chronic schistosomiasis. In mice infected with S. mansoni, we identified granulocytosis within the spleen including increased eosinophils, neutrophils, basophils, and mast cells. Additionally, ILC2s and dendritic cells were increased. The cytokine data suggests an IL33-independent mixed Th1/Th2 response with upregulation of granulocyte proliferative and recruitment factors. The late-stage chronic schistosomiasis case study identified blood neutrophilia and eosinophilia but with absent basophils. These data enhance our understanding of the complex immune response that occurs with schistosomiasis and may offer new insights to support therapeutic strategies against this important disease.